Precision of the models of Altman, Springate, Zmijewski, and Grover for predicting the financial distress - M. Fakhri Husein; Galuh Tri Pambekti (Journal of Economics, Business, and Accountancy Ventura, 2014)
Financial distress models need to be developed as a model of an early warning system. Such an effort is intended to anticipate the conditions that can lead to the bankruptcy of the company. This study aims to analyze the accuracy of the model of Altman, Springate, Zmijewski, and Grover as the best predictor of financial distress. This research is a quantitative study in which the data were collected by means of a data pool. This is done by using a dummy variable. The sample consists of 132 companies which are listed on the list of Daftar Efek Syariah (DES) in 2009-2012. The analysis isdone by using an analytical tool that is a Binary Logistic Regression. It shows that the model of Altman, Zmijewski models, Springate, and Grover can be used for prediction of financial distress. However, the model of Zmijewski is the most appropriate model to be used for predicting the financial distress because it has the highest level of significance compared to the other models. Zmijewski model is used for having more emphasis on the leverage ratio as an indicator of financial distress.